Experimental and numerical studies on heat transfer characteristics of vertical deep-buried U-bend pipe in intermittent heating mode. (May 2019) - Li, Chao; Guan, Yanling; Wang, Xing; Zhou, Cong; Xun, Yingjiu; Gui, Lingping
Highlights: Depth of geothermal energy to supply heat in buildings exceeded 2500 m. Heat transfer performance of the pipe was evaluated by in-situ intermittent tests. A full-scale numerical model was established and experimentally validated. Heat transfer performance of the pipe under typical heating modes was studied. Abstract: Using a deep-buried U-bend pipe with a depth of 2505 m, the heat transfer characteristics of a deep-buried pipe system for typical buildings under intermittent heating condition were evaluated by in-situ intermittent tests. The entire test duration was 3 days (72 h). The intermittent heating mode for residential buildings was as follows: The system was operated every day during 5:00–11:00 in the morning and between 16:00 in the afternoon and 24:00 at midnight. Based on the in-situ tests, a three-dimensional (3D) full-scale numerical simulation model combining the heat transfer processes inside and outside the pipe was established and verified for the intermittent operation. By using the test data and numerical simulation, the heat transfer performances of deep-buried U-bend pipes for residential buildings in Xi'an were analyzed during the heating season under both continuous and intermittent heating modes. Moreover, the heat transfer characteristics of deep-buried U-bend pipes for typical commercial and office buildings under the intermittent heating mode were analyzed.